2016
DOI: 10.1063/1.4960198
|View full text |Cite
|
Sign up to set email alerts
|

Polarization conversion of metasurface for the application of wide band low-profile circular polarization slot antenna

Abstract: In this letter, based on a corner-cut square metasurface, a planar polarization conversion structure is presented and the application for wide band low-profile circular polarization (CP) slot antenna is proposed. The mechanisms for achieving the CP state from a linearly polarized incident wave and for broadening the working bandwidth of conventional slot antenna are analyzed theoretically. The wide band low-profile CP slot antenna is achieved with numerical optimizations and parameter studies. Both simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(55 citation statements)
references
References 20 publications
0
55
0
Order By: Relevance
“…In general, the operation principle of most loop‐like CP antennas is to simultaneously excite the 2 orthogonal linearly polarized (LP) modes with equal amplitude and in quadrature‐phase with by various perturbations. When such antennas are cavity‐backed and designed as uni‐directional antennas, it is found that the front‐to‐back ratio is <20 dB . Meanwhile, most of these antennas still exhibit relatively complicated structures with many design parameters .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the operation principle of most loop‐like CP antennas is to simultaneously excite the 2 orthogonal linearly polarized (LP) modes with equal amplitude and in quadrature‐phase with by various perturbations. When such antennas are cavity‐backed and designed as uni‐directional antennas, it is found that the front‐to‐back ratio is <20 dB . Meanwhile, most of these antennas still exhibit relatively complicated structures with many design parameters .…”
Section: Introductionmentioning
confidence: 99%
“…When such antennas are cavity-backed and designed as uni-directional antennas, it is found that the front-to-back ratio is <20 dB. 22,[30][31][32][33] Meanwhile, most of these antennas still exhibit relatively complicated structures with many design parameters. [30][31][32]34 Therefore, it is a challenging task to design a loop-like CP antenna with a high front-to-back ratio while maintaining a relatively simple loop-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polarization conversion characteristic of MS has been employed to design CP antenna with linearly polarised (LP) source . For instance, a Fabry‐Perot resonant cavity using PRS based on polarization conversion MS with LP patch antenna for CP radiation and high gain is introduced in, but the distance requirement between PRS and source increases overall volume of antenna.…”
Section: Introductionmentioning
confidence: 99%
“…The electrically thick substrates in the THz frequency cause serious problems, such as substrate reso-nance, which can be eliminated by decreasing the substrate thickness up to λ o /20, where λ o is a free space wavelength [11]. In recent years, researchers have demonstrated many extraordinary properties of metasurface antennas [12][13][14][15][16][17] because of their potential to provide the novel characteristics of an ultra-low profile and enhanced performance in gain, radiation pattern, and bandwidth [18]. Metasurface antennas have their own intrinsic advantages of easy fabrication, low cost, light weight, and extreme flatness.…”
Section: Introductionmentioning
confidence: 99%